Assessment of Utilization Possibilities of Heat Conducted by Waste Gases Exhaust Pipe of SB 1.5 Drum Drier for Drying Wood Chips (Agricultural Engineering, 2016)
Based on the exploitation research, the authors evaluated the possibilities of using the heat conducted through the side surface of the waste gases exhaust pipe of SB 1.5 drum drier for drying wood chips. According to the estimated calculations within one hour approximately 173 thousand of kJ of heat may be obtained from the external surface of the waste gases exhaust pipe with the height of 7 m and temperature of approximately 78°C which constitutes an equivalent of approximately 4 kilo of heating oil. In case the above mentioned heat source for drying wood chips in SPA 20 silo with a volume of 6800 kilo within 50% to 20% humidity is used, one may expect that the drying time will be approximately 100 hours.